I vaccini: la necessità di una comunicazione strategica per ricostruire un rapporto di fiducia con i cittadini e sconfiggere la deriva delle fake news - Andrea Altinier (Culture e Studi del Sociale)
Scientific communication today is experiencing a difficult transition, but the need to rethink one?s model to counteract the phenomenon of fake news and its effects is essential. Strategic communication is the answer to build a dialogue and a relationship with public opinion and to re-establish correct information on a sensitive issue such as that of vaccines. The flow of contents and fake news of the no vax can be defeated only with a long-term vision and able to field a counter flow of contents able to defuse the phenomenon of the eco-chambers and the spiral of silence. A complex challenge that requires method, model and strategy.